WEDA DALAM KEHIDUPAN MASYARAKAT HINDU JAWA - Sujaelanto (Widya Aksara, 2019)
The Vedas are Hindu scriptures whose values ??must be believed. Thousand-year-old Vedas come from the mainland of the Sindhu river valley and spread to all corners of the world, not to mention that Indonesia also received the influence of the teachings of the Vedas. Vedic values ??are critical to the local culture so that it further strengthens the foundation of civilization. In Indponesia, the Vedas became a foothold for the Hindu occupation. In Java the vedas were adopted not only as holy books, but also as valuable knowledge. The concept of Vedas is widely used by Javanese people to mark truth, or to point to a place. The Hindu community in Java, explores the vines not only through the form of ceremonies, but also becomes part of the lifestyle and symbol of diversity. Vedic verses are not much displayed in the corner of the family room or temple, but the reflection of the Vedic value echoes in the joints of Javanese society. Hndu in Java slowly began to revitalize the values ??of the Vedic teachings through Dharmagita activities, pesantian, pasraman activities, Hindu young generation actions. In order to echo the teachings of the Vedas need synergistic work between religious leaders, families, religious assemblies to formally elevate the Vedic scriptures.